Pengukuran Akurasi Arah Kiblat Masjid Menggunakan Qiblat Tracker RHI di Desa Angkue - Nurul Wakia; Ayyub Fudhail Zibly; Syarifah Febby Amelia; Nur Aisyah; Nur Afia; Mauliana Adwiah; Rahmadani; Andi Sultan Metaraga Agung; Siti Nurhaliza Jufri (Pangulu Abdi: Jurnal Pengabdian Kepada Masyarakat, 2022)
Abstract Angkue Village is one of the villages in Kajuara District, Bone Regency which is located in the coastal area. The majority of people in Angkue Village adhere to Islam and have dense poverty levels and have middle to upper economic levels.Even though Angkue Villageis a coastal area, we cannot know that the Qibla direction of the Jami Taqwa Mosque is deviated 8° Southwest. Reffering to these problems, we conducted a Qibla direction verification at the Jami Taqwa Mosque with the Hisab Ruqyat Team of the Ministry of Religion, Bone Regency. Keywords : Qibla direction; Angkue Village; Jami Taqwa Mosque